Pengaruh Pemberian Permen Jahe Terhadap Penurunan Mual Muntah Pada Ibu Hamil Trimester I - Nabila Asyahida; Enny Yuliaswati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
The incidence of nausea and vomiting in Indonesia during 2019 there were 543 pregnant women in Lampung Province in 2019 there were 50-90% of 19,896 pregnant women experiencing nausea and vomiting. The impact of nausea and vomiting if not handled properly will cause severe nausea and vomiting. Ginger has the property of providing anti-nausea effects, giving ginger preparations in the form of candy is more effective in reducing the side effects of ginger such as an unpleasant taste in the mouth. Objective; To determine the effect of giving ginger candy on reducing nausea and vomiting in pregnant women in the first trimester. Method; Pre-experimental with a one group pretest-posttest design. The sample in this study was 32 people. The sampling technique used simple random sampling. The research instrument used the Pregnancy Unique Quantification of Emesis and Nausea (PUQE) scoring system questionnaire. Statistical tests using the Wilcoxon test. Results; There is a difference in reducing nausea and vomiting before and after being given ginger candy with a p-value of 0.000 <0.05. Conclusion; There is an effect of giving ginger candy on nausea and vomiting in pregnant women in the first trimester.